The Powder Trust, 1872-1912 - Stevens, William S. (Quarterly Journal of Economics, 1912)
Introduction, 444. — Period I. Organization of the first combination in the explosives trade, 445. — The Council, 446. — Compacts with the California Powder Works, 447. — Amendment of the Articles of Association, 448. — The Agreement of 1886, 450. — Fundamental Agreement of 1889, 452. — Period II. Competition between 1890 and 1894, 454. — Revision of the Fundamental Agreement, 456. — The "Understanding" of 1896, 456. — Advance in the prices of powder subsequent to 1896, 457. — Contests against new competitors, 459. — Miscellaneous agreements looking to more complete control, 460. — Early combination in the Dynamite Trade, 462. — Acquisitions of the Eastern Dynamite Company, 465. — Origin of the European Agreement, 465. — Its terms, 466. — The Mexican Agreement, 467. — Period III. The organization of E. I. du Pont de Nemours and Company, Delaware Corporation of 1902, 470. — Relation of E. I. du Pont de Nemours and Company and Laflin and Rand to subsidiaries, 471. — Option upon Laflin and Rand, 472. — The Delaware Securities Company, 472. — The Delaware Investment Company, 473. — Relations of the Companies outside of the combination, 474. — E. I. du Pont de Nemours and Company of Pennsylvania, 475. — The California Investment Company, 476. — International Smokeless Powder and Chemical Company, 477. — Percentage of control exercised, 478. — Prices, 478. — Dissolution of subsidiaries, 479. — Decision of the Circuit Court, 480.